Pengaruh Adversity Quotient dan Resiliensi Terhadap Kemampuan Berpikir Kritis Siswa Kelas IXA pada Materi SPLDV - Clara Desy; Ahmad Yani T; Revi Lestari Pasaribu (Kilau Publishing, 2026)
This study was motivated by students’ low critical thinking ability in learning Systems of Linear Equations in Two Variables. Critical thinking is an essential skill in mathematics learning because it enables students to analyze, evaluate, and solve problems logically. Several factors influence students’ critical thinking ability, including Adversity Quotient and resilience. Adversity Quotient refers to students’ ability to deal with difficulties, while resilience relates to students’ ability to adapt and recover from academic challenges. This study aimed to determine the effect of Adversity Quotient and resilience on students’ critical thinking ability in the topic of systems of linear equations in two variables. This study used a quantitative approach with a causal associative (ex post facto) design. The sample consisted of 29 students of class IXA at SMP Negeri 1 Pontianak. Data were collected through questionnaires and essay tests. Data analysis included validity, reliability, classical assumption tests, hypothesis testing, and coefficient of determination. The results showed that Adversity Quotient had an effect on students’ critical thinking ability. Resilience also had an effect on students’ critical thinking ability. Simultaneously, both variables significantly affected students’ critical thinking ability with a coefficient of determination of 0.485 or 48.5%. These findings indicate that Adversity Quotient and resilience contribute significantly to improving students’ critical thinking ability in mathematics learning.